An Analysis of Visual Design Strategies for Instagram Content: Five Monkeys Burger as a Promotional Medium - Syifa Naura Agustina; Arif Fiyanto (Gorga : Jurnal Seni Rupa, 2025)
This study aims to analyze the visual design strategy applied by Five Monkeys Burger in Instagram content as a means of digital promotion aimed at Generation Z. The approach used is qualitative descriptive. Data was collected through online observation of Instagram content in feeds, stories, and reels, accompanied by documentation studies, literature reviews, and questionnaire distribution to 51 respondents aged 18–25 years to support the findings. The data analysis technique uses the Visual Content Analysis technique. The results showed that the visual strategy of Five Monkeys Burger was consistently displayed through the selection of contrasting color palettes, typography, flat design illustrations, and structured layouts. Observations and questionnaires indicate that this visual approach has succeeded in forming a strong brand identity, attracting the target audience's attention, and increasing user engagement compared to similar competitors. Visual design strategies that are designed adaptively and aligned with audience preferences play an important role in strengthening the effectiveness of digital promotion on social media platforms. This study provides practical implications for MSMEs in building a strong brand identity through planned and consistent visual design.